Pharmacotherapy, Resource Needs, and Physician Recruitment Practices in Substance Use Disorder Treatment Programs. Issue 1 (January 2019) - Knudsen, Hannah K.; Brown, Randy; Jacobson, Nora; Horst, Julie; Kim, Jee-Seon; Collier, Elizabeth; Starr, Sanford; Madden, Lynn M.; Haram, Eric; Molfenter, Todd
Abstract : Objectives: Effective pharmacological treatments for opioid use disorder (OUD) continue to be underutilized, particularly within specialty substance use disorder (SUD) treatment organizations. Few studies have examined whether specific practices to recruit prescribers, financial needs, and human resource needs facilitate or impede the implementation of pharmacotherapy. Methods: Surveys were completed by administrators from 160 treatment programs in Florida, Ohio, and Wisconsin. Respondents described availability of five pharmacotherapies for treating OUD, organizational resource needs, current use of physician recruitment practices, and buprenorphine treatment slots. Results: The mostly commonly available medications were injectable naltrexone (65.4%; n = 102), buprenorphine-naloxone (55.7%; n = 88), and tablet naltrexone (50.0%; n = 78). Adopters of each of the 5 pharmacotherapies reported significantly greater physician outreach than organizations that did not provide these medications. The mean number of buprenorphine slots was 94.1 (SD 205.9). There were unique correlates of adoption (ie, any slots) and availability (number of slots) of buprenorphine. Physician outreach activities were correlated with the likelihood of nonadoption, whereas medical resource needs (ie, needing more physicians to prescribe pharmacotherapy) and dedicated resources for physician recruitment were associated with the number of slots. Conclusions: Physician recruitment activities differentiated those organizations that had existing pharmacotherapy treatment capacity (ie, any slots) from those that had no capacity. Efforts to address the medical resource needs of treatment organizations, and also strategies that encourage organizations to devote resources to recruiting prescribers may hold promise for increasing access to these lifesaving treatments.